2016
DOI: 10.1017/s1431927616005432
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Nanoscale Three-Dimensional Mass-Density Autocorrelation Function of Individual Cells

Abstract: Interrogating cellular nano-architecture may help reveal previously unknown structure-function relations. The three-dimensional mass-density distribution plays an important role in quantifying cellular structure. For instance, chromatin structure can be directly represented by the mass-density, as the individual molecules have similar mass and larger density generally indicates higher level of compaction. Chromatin compaction, in turn, is associated with gene transcription and is crucial in various aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…By analyzing the HAADF movie of sequential scans, where the signal intensity quantified the projected mass for each pixel, [54][55][56] it was revealed that the polymer is non-uniformly removed by electron irradiation at the nanoscale. At the beginning of the movie, the width of the polymer features gradually shrank, and voids were generated with lower signal intensity (Figure 3A, first row; and Figure 3B, stage 1) creating thin (~10 nm wide) polymer filaments that were then rapidly removed (Figure 3A, middle row; and Figure 3B, stage 2).…”
Section: Polymer Evaporation Induced By Electron Irradiationmentioning
confidence: 99%
“…By analyzing the HAADF movie of sequential scans, where the signal intensity quantified the projected mass for each pixel, [54][55][56] it was revealed that the polymer is non-uniformly removed by electron irradiation at the nanoscale. At the beginning of the movie, the width of the polymer features gradually shrank, and voids were generated with lower signal intensity (Figure 3A, first row; and Figure 3B, stage 1) creating thin (~10 nm wide) polymer filaments that were then rapidly removed (Figure 3A, middle row; and Figure 3B, stage 2).…”
Section: Polymer Evaporation Induced By Electron Irradiationmentioning
confidence: 99%